Weed seed mass affects seedling establishment and resource allocation patterns across a cereal rye surface residue gradient. (16th December 2021) - Ficks, Teala S.; Lowry, Carolyn J.; Wallace, John M.
Abstract: Knowledge of weed population‐ and community‐level responses to the integration of cover crop surface residues (CCSRs) is vital to understanding their value when integrated into no‐till field crop production systems. Ecological theory suggests that weed seedling survival and resource allocation patterns during the establishment phase should be influenced by the interaction between seed mass and CCSR levels. We conducted a greenhouse experiment to investigate seedling establishment rates and resource allocation patterns in response to increasing CCSR levels across a seed mass gradient, including weed and crop species. The experiment utilised a two‐factor treatment structure, including 10 plant species that varied in seed mass by three orders of magnitude and four cereal rye mulch levels (0, 3360, 6720 and 10, 080 kg ha −1 ). Our results support the hypothesis that the effect of CCSRs on seedling establishment rates is a function of seed mass. Analysis by species showed a decrease in seedling establishment rates of dicotyledon species across all CCSR levels, but this relationship varied among monocotyledon species. CCSR levels were positively correlated with resource allocation to the hypocotyl and specific hypocotyl length of dicotyledon species. Increasing CCSR levels decreased allocation of resources to roots in broadleaved species but did not affect resource allocation patterns in monocotyledon species. We conclude that the combined effects of CCSRs on seedling establishment rates and resource allocation could significantly influence weed population‐ and community‐level dynamics.